The importance of the dental surgeon in the diagnosis of lesions and abuses in childhood and adolescence (Research, Society and Development, 2023)
With the societies that have been built over the years around the world, problems of a psychological, social and physical nature have been emerging and developing in an abrupt and extensive way. Among them, maltreatment against children and adolescents stands out, in which the dentist has a very important role in identifying its manifestations in the head, neck and oral cavity. This study aimed, through a systematic literature review, to characterize, define, alert, diagnose, define and add to the reader's knowledge about the distinguished role of the dental surgeon in the diagnosis of injuries and abuse not only in childhood. but also in adolescence. To obtain the necessary data, a bibliographical research was carried out in the databases of thcle most relevant Faculties in Brazil, as well as in the already prestigious literature on the subject, as well as in the current Laws. Only original scientific articles were included, in Portuguese, English and Spanish, considering the period from 1991 to 2020. In total, 270 studies were selected, and of these, only 51 were selected because they met the inclusion criteria. Regrettably due to the lack of attention and even knowledge by health professionals, both psychological and physical diagnoses of abuse injuries become complex and tortuous, which leads to even greater repression of victims of these aggressions.